Principles of water and wastewater treatment processes - Stuetz, R. (Richard); International Water Association (London : IWA Pub., 2009)
"Principles of Water and Wastewater Treatment Processes outlines the principle unit operations that are involved in the separation, degrada tion and utilsation of organic and inorganic matter during water and wa stewater treatment. It is designed for individual, self-paced study tha t describes the form, function and application of unit operations for t he treatment of water and wastewater. Each section of the text provides step-by-step learning, the key points that highlight the principles in volved, exercises to aid understanding, self-assessment questions, text references. It is organised so that the reader can learn in their own time."--Back cover.
Water quality -- Flowsheeting -- Physical processes -- Chemical proc esses -- Sorption processes -- Biological processes -- Membrane process es -- Sludge treatment and utilisation -- Odour management.
Previous version published: 2003 with the same ISBNs.
Includes bibliographical references.
Keywords: Water -- Purification; Sewage -- Purification